Endoscopic papillectomy: a novel approach to difficult cannulation. Issue 1 (July 1996) - Farrell, R J; Khan, M I; Noonan, N; O'Byrne, K; Keeling, P W
Abstract : BACKGROUND: Selective cannulation of the biliary and pancreatic ducts is considered to be the most difficult and rate limiting aspect of diagnostic endoscopic retrograde cholangiopancreatography (ERCP). AIMS/METHODS: A novel technique for difficult cannulation is described and its potential role in relieving malignant duodenal obstruction secondary to ampullary carcinoma. A diagnostic endoscopic papillectomy was performed in 10 patients in whom previous attempts at cannulation had failed. Five patients had exophytic ampullary carcinomas, one had carcinoma of the head of pancreas, two had an oedematous ampulla secondary to low common bile duct stones, while two had protuberant ampullae with ectopic orifices. The technique entails snaring the ampulla flush with the duodenal wall using a polypectomy snare and in a similar fashion to polypectomy removing the ensnared ampulla with diathermy using a coagulation current. The underlying exposed ducts can then be cannulated while the ensnared ampulla can be retrieved to aid histological diagnosis. RESULTS: Successful cannulation was achieved in all 10 cases with significant haemorrhage in one patient (10%). Four of the snared ampullary carcinomas (80%) were retrieved enabling a histological diagnosis to be made. CONCLUSIONS: This study demonstrates the potential role for endoscopic papillectomy as a means of cannulation in difficult circumstances, however larger comparative studies are required.